Air Quality Analysis in the Vicinity of Tanjung Lesung Beach, Banten - Widianti, Riskia Chandra; Syaifullah, Mhd Muslim; Hanifah, Sarina; Mulyanah, Annisa (Jurnal Riset Sains dan Kimia Terapan, 2025)
Beaches are among the most popular recreational destinations for the public. This study aims to evaluate the air quality in the Tanjung Lesung coastal area, Pandeglang, Banten, by collecting air samples followed by laboratory analysis. The air pollutants measured in this study include Total Suspended Particulate (TSP), Sulfur Oxides (SOx), and volatile organic compounds such as Benzene, Toluene, and Xylene (BTX). Sampling methods employed were the impinger method for SOx, High Volume Air Sampler(HVAS) for TSP and Pb, and activated carbon and XAD adsorbents for BTX. The results showed that the concentration of TSP reached 421.08 µg/m³, exceeding the national ambient air quality standard of 230 µg/m³. The concentration of SOx was recorded at 0.7837 ppm, which remains within the permissible limit. Meanwhile, BTX compounds were not detected in the air samples, likely due to very low concentrations. These findings suggest that although the coastal air is relatively free from volatile organic compounds, a high level of particulate pollution was observed, which is suspected to originate from nearby industrial activities. Regular air quality monitoring is essential to ensure public health and maintain the comfort of tourist environments.